Exposure to lard-based high-fat diet during fetal and lactation periods modifies breast cancer susceptibility in adulthood in rats - Andrade, Fabia de Oliveira; Fontelles, Camile Castilho; Rosim, Mariana Papaleo; Oliveira, Tiago Franco de; Melo Loureiro, Ana Paula de; Mancini-Filho, Jorge; Rogero, Marcelo Macedo; Moreno, Fernando Salvador; Assis, Sonia de; Barbisan, Luiz Fernando [UNESP]; Hilakivi-Clarke, Leena; Ong, Thomas Prates (Elsevier B.V., 2014)
The present study investigated whether early life exposure to high levels of animal fat increases breast cancer risk in adulthood in rats. Dams consumed a lard-based high-fat (HF) diet (60% fat-derived energy) or an AIN93G control diet (16% fat-derived energy) during gestation or gestation and lactation. Their 7-week-old female offspring were exposed to 7,12-dimethyl-benzo[a]anthracene to induce mammary tumors. Pregnant dams consuming an HF diet had higher circulating leptin levels than pregnant control dams. However, compared to the control offspring, significantly lower susceptibility to mammary cancer development was observed in the offspring of dams fed an HF diet during pregnancy (lower tumor incidence, multiplicity and weight), or pregnancy and lactation (lower tumor multiplicity only). Mammary epithelial elongation, cell proliferation (Ki67) and expression of NF kappa B p65 were significantly lower and p21 expression and global H3K9me3 levels were higher in the mammary glands of rats exposed to an HF lard diet in utero. They also tended to have lower Rank/Rankl ratios (P=.09) and serum progesterone levels (P=.07) than control offspring. In the mammary glands of offspring of dams consuming an HF diet during both pregnancy and lactation, the number of terminal end buds, epithelial elongation and the BCL-2/BAX ratio were significantly lower and serum leptin levels were higher than in the controls. Our data confirm that the breast cancer risk of offspring can be programmed by maternal dietary intake. However, contrary to our expectation, exposure to high levels of lard during early life decreased later susceptibility to breast cancer. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Breast cancer; High-fat diet; Fetal programming; RANK/RANKL pathway; H3K9me3